The Effectiveness of Audiovisual Media Management in Improving Students' Badminton Footwork Skills - Aidil Syaputra; Zainur, Zainur; Hirja Hidayat; Arfa Adha; Purwanto, Purwanto; Rahmad Diyanto (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2025)
Footwork skills are a fundamental aspect of badminton because they determine the efficiency of movement and the effectiveness of shots. However, many students still have difficulty mastering this technique. This study aims to analyze the effectiveness of audio-visual media in improving badminton footwork skills. The study used a quasi-experimental method with a pretest–posttest control group design. The research sample consisted of 73 Physical Education, Health, and Recreation students at the University of Riau in the even semester of 2024/2025, divided into an experimental group (n=37) and a control group (n=36). The research instrument was a badminton footwork test that had been validated by experts. The analysis results showed an increase in footwork skills in both groups, with the average gain in the experimental group (+1.57) higher than that in the control group (+1.06). The paired t-test showed a significant increase in the experimental group (p=0.002), but the independent t-test showed that the difference between the groups was not significant (p=0.052). These findings indicate that audio-visual media can be an effective complement to footwork learning, although it does not completely replace conventional methods.